2010
DOI: 10.1002/etc.271
|View full text |Cite
|
Sign up to set email alerts
|

Selenium accumulation in coturnix quail fed seleno‐L‐methionine

Abstract: The accumulation of selenium in Coturnix quail, a sensitive species to selenium toxicity, was studied. Quail were fed diets containing 0.7 µg/g (control), 12 µg/g (low-Se), and 22 µg/g (high-Se) as seleno-L-methionine for four weeks. At the end of the four weeks, blood selenium in the treatment groups had a positive significant relationship to diet, and selenium in blood was approximately two times, and in livers was approximately three times, the dietary concentration. Quail in the low-Se group accumulated se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
1
Order By: Relevance
“…Unlike other species studied, accumulation of Se in quail blood did not plateau but continued to increase until the study ended [45]. Body mass, as a percentage of initial body mass, was similar in the control and low-Se groups (102%) but lower in the high-Se group (97%).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Unlike other species studied, accumulation of Se in quail blood did not plateau but continued to increase until the study ended [45]. Body mass, as a percentage of initial body mass, was similar in the control and low-Se groups (102%) but lower in the high-Se group (97%).…”
Section: Discussionmentioning
confidence: 60%
“…Liver mass, as a percentage of initial body mass, showed a positive dose-dependent response to dietary Se, and liver mass was significantly higher in quail fed 22 mg Se/g than in control quail. Unlike other species studied, accumulation of Se in quail blood did not plateau but continued to increase until the study ended [45]. The enlarged livers of small wild mice trapped in the Se-enriched Kesterson Reservoir [21] indicate that these mice suffered from high levels of acute Se toxicity manifested as hepatomegaly and higher liver Se concentrations.…”
Section: Discussionmentioning
confidence: 83%
“…20,21 Nevertheless, Santolo et al reported no mortalities in Coturnix quails fed with a diet containing SeMet at 22 mg Se g À1 for four weeks. 22 On the other hand, an increase in serum ALT was observed in mallards fed with sodium selenite and SeMet at concentrations of 3.5 and 2.2 mg mL À1 , respectively, for 12 weeks. 23 Although no serum biochemical indices were determined, no apparent adverse effects, including death, decrease in body and tissue/organ weight, and depilation, were observed in the quails during the experimental period.…”
Section: Se Distribution In the Japanese Quail Bodymentioning
confidence: 96%
“…Ця субстанція є біологічно активним промотором регуляції спермоплазми та субстратів простатовезикулярного комплексу з участю у регуляції нормального рівня рН. Селен-метіонін є важливою біологічно речовиною, що відіграє роль амінокислоти та мікроелементу, яка підтримує антиоксидатні процеси в різних структурах організму людини, в тому числі і тканинах ПЗ та яєчок [22][23][24][25].…”
Section: анализ эффективности различных видов консервативной терапии ...unclassified